Metode-Metode Optimasi Memcached sebagai NoSQL Key-value Memory Cache - Mandahadi Kusuma (UIN Sunan Kalijaga Yogyakarta, 2019)
Memcached is an application that is used to store client query results on the web into the memory server as a temporary storage (cache). The goal is that the web remains responsive even though many access the web. Memcached uses key-value and the LRU (Least Recenly Used) algorithm to store data. In the default configuration Memcached can handle web-based applications properly, but if it is faced with an actual situation, where the process of transferring data and cache objects swells to thousands to millions of items, optimization steps are needed so that Memcached services can always be optimal, not experiencing Input / Output (I / O) overhead, and low latency. In a review of this paper, we will show some of the latest research in memcached optimization efforts. Some methods that can be used are clustering are; Memory partitioning, Graphic Processor Unit hash, User Datagram Protocol (UDP) transmission, Solid State Drive Hybird Memory and Memcached Hadoop distributed File System (HDFS)Keywords : memcached, optimization, web-app, overhead, latency